The Development of the Museum Fansuri Bongal Site in Jago-Jago Village, Central Tapanuli Regency, 2023–2025 - Epridasari Batubara; Abdi Mubarak Syam (Local History & Heritage, 2026)
This study examines the institutional development of the Fansuri Museum at the Bongal Site in Central Tapanuli during 2023–2025, with particular emphasis on community-based heritage preservation and museum governance. Previous studies on the Bongal Site have predominantly focused on archaeological discoveries and maritime trade networks. At the same time, the emergence of local museums as community-driven heritage institutions has received comparatively limited scholarly attention. This qualitative field study employed direct observation, in-depth interviews with museum administrators and local communities, and document analysis as its primary data sources. The findings reveal that the establishment of the museum was closely associated with public concerns regarding the loss of archaeological artefacts resulting from mining activities in the Bongal area. Between 2023 and 2025, the museum underwent gradual institutional development through more systematic collection management, expanded educational programs, and strengthened public participation in heritage-related activities. The study further identifies several persistent challenges, including limited conservation infrastructure, limited financial capacity, and limited availability of professional museum management. This research demonstrates that the Fansuri Museum functions not merely as a repository of historical artefacts but also as a community-based heritage institution that reinforces local historical consciousness and promotes cultural education within coastal communities.